"Conselhos e instruções a ti, professor” : a imprensa pedagógica da Paraíba como lugar de atuação e formação docente em torno das ideias renovadoras (1919-1942) - Biserra, Ingrid Karla Cruz (2019)
This doctoral thesis linked to the area of the History of Education aimed to analyze the pedagogical press of Paraiba as a space of action and teacher training in favor of the construction of pedagogical renewal ideas between 1919-1942. Our main historical sources were the Bulletin of the Society of Primary Teachers of Paraiba (1919), the newspaper O Educador (1921-1922) and the Magazine of Teaching (1932-1942). We started from the understanding that the pedagogical press was the stage used by teachers to give legitimacy and scientific theories to their ideas, seeking a space of their own performance and, at the same time, training for other subjects. It was a necessary material support for the educational renovation project. Its pages included pedagogical ideas, teaching methods, instructions, communiques, guidelines, lesson plans, lectures, photographs and graphic resources, which fostered the discussion of the knowledge that aimed to form the faculty, especially the primary school. This type of printing was an instrument of political action of the intellectual teachers who used their networks of sociability, as well as strategies and tactics to print and to make representations (ALONSO 2002, CERTEAU, 1990, CHARTIER, 1990, SIRINELLI, 2003). The proposal was clear: it was necessary to establish a renovated school in Paraiba. Laws, associations, pedagogical weeks, bulletins, newspapers and magazines fostered the changes and were analyzed in this research from the encounter between the "old" and the "new", the "traditional" and the "modern". There was no ready formula to call the educational renewal of the period, and everyone, even participants in the same group, thought differently. We can say, then, that there were several versions of the new schools defended, because the ideas were not static. On the contrary, they were in motion. Being aware of these nuances was one of our intentions. In the midst of their advice and instruction, these subjects created an intellectual field and under the sign of the new, the teachers acted and formed their professional colleagues in the pedagogical press.